1999
DOI: 10.1093/jae/8.1.87
|View full text |Cite
|
Sign up to set email alerts
|

How instability lowers African growth

Abstract: This paper aims to assess the role of instabilities on Africa low rates of growth during the seventies and eighties, using cross-section econometric estimates, on a sample of African and non African countries and two pooled decades. Africa exhibits higher "primary" instabilities (climatic, terms of trade and political instabilities), i.e. instabilities which are structural rather than the result of policy. These "primary" instabilities influence Africa growth, through a lower growth residual more than a lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 25 publications
2
41
0
5
Order By: Relevance
“…In an earlier study, we estimate the influence of several primary instabilities, mainly exogenous, on the rate of growth, and argue that these instabilities, significantly higher in Sub-Saharan Africa than in other developing countries, may have been a major factor in the region's slow growth rate during the 1970s and 1980s: these instabilities are the instability of the terms of trade, weighted by the average export-to-GDP ratio, or that of the real value of exports, similarly weighted, the instability of the agricultural value added (weighted by the average share of agricultural value added in GDP) and political instability. The first and the third factors appear to have a significant effect on growth, but not that of the agricultural value added (Guillaumont et al 1999). However, in another study, instability of both real value of exports and agricultural value added (unweighted here) appears to be significant (Guillaumont and Chauvet 2001).…”
Section: Primary Versus Intermediate Instabilitiesmentioning
confidence: 62%
“…In an earlier study, we estimate the influence of several primary instabilities, mainly exogenous, on the rate of growth, and argue that these instabilities, significantly higher in Sub-Saharan Africa than in other developing countries, may have been a major factor in the region's slow growth rate during the 1970s and 1980s: these instabilities are the instability of the terms of trade, weighted by the average export-to-GDP ratio, or that of the real value of exports, similarly weighted, the instability of the agricultural value added (weighted by the average share of agricultural value added in GDP) and political instability. The first and the third factors appear to have a significant effect on growth, but not that of the agricultural value added (Guillaumont et al 1999). However, in another study, instability of both real value of exports and agricultural value added (unweighted here) appears to be significant (Guillaumont and Chauvet 2001).…”
Section: Primary Versus Intermediate Instabilitiesmentioning
confidence: 62%
“…Relative to other regions, SSA is especially susceptible to climatic and agricultural risk and especially vulnerable to terms of trade shocks, famines, political conflict, droughts and, more recently, floods. Guillaumont, Guillaumont-Jeanney and Brun (1999) find that SSA has higher levels of primary instabilities (political, climatic and terms of trade) than other developing-country regions. Such vulnerability is a source of 'economic uncertainty' that may reduce growth rates and help to explain aid ineffectiveness.…”
Section: Transmission Mechanismsmentioning
confidence: 81%
“…Gyimah-Brempong and Traynor (1999) find that political instability has a direct negative effect on growth and also an indirect effect via discouraging investment. Guillaumont, Guillaumont-Jeanney and Brun (1999) find that primary instabilities in SSA reduce growth by distorting economic policy; the rate of investment is volatile, hence the growth rate is lowered. As discussed in the next section, by including policy indicators (notably inflation), a political variable and investment in our specification we hope to pick up some of these effects.…”
Section: Transmission Mechanismsmentioning
confidence: 98%
“…Easterly and al [1993], who analyzed the differences in long-term growth in a panel of countries, found that the impact of terms of trade instability play an important role in explaining the variance of the growth. Guillaumont and Brun [1999] tested the effect of volatile terms of trade on economic growth. Their results show that the effects of shocks of terms of trade on economic growth are more important and significant in the countries of subSaharan Africa than in other developing countries.…”
Section: Review Of Literaturementioning
confidence: 99%